Hi, I am beginner in mathematics , I have the following three relationships:

a=b

c=d

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

Hi, I am beginner in mathematics , I have the following three relationships:

a=b

c=d

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

a=b

c=d

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

can I use any other formulas?!!

They gave you c=d. Can't you just use d?Hi, I am beginner in mathematics , I have the following three relationships:

a=b

c=d

a-b=c-d

I need to calculate c under the assumption that a, b and d are known values.

I got c=a-b+d

and c=a/b*d

BTW: a=b so a-b=0 & c=d so c-d=0. What was the original question??